Методологічні основи кластерного підходу в інноваційних проектах - Пітерська, Варвара Михайлівна (НТУ "ХПІ", 2018)
Розроблені теоретичні основи та методичні положення застосування кластерного підходу при реалізації інноваційних проектів. Було визначено показники оцінки рівня науково-технологічного розвитку при управлінні інноваційними проектами, встановлено критерії інноваційної кластеризації та сформовані методологічні основ визначення цінності проектно-орієнтованої організації при створенні кластерів в рамках виконання інноваційних проектів. Вирішення цих завдань потребує створення системи чіткої взаємодії держави, бізнесу, науки та освіти на основі використання ефективних інструментів управління проектами в рамках інноваційного розвитку, серед яких важливу роль має відігравати кластерний підхід. При цьому було визначено синергетичний ефект взаємодії учасників інноваційного проекту та створена карта кластеру роботи науково-дослідних та бізнесових організація, що приймають участь у реалізації інноваційних проектів.

There are theoretical bases and methodological positions of the application of the cluster approach for the implementation of innovative projects. There were determined the indicators for assessing of the level of scientific and technological development in the innovation projects management, there were established the criteria for innovative clustering, there were formed the methodological foundations for determining of the value of the project-oriented organization while creating clusters within the framework of innovative projects. At the same time, there was determined a synergistic effect of the interaction between the participants of the innovation project and there was created a cluster map of the work of research and business organizations engaged in the implementation of innovative projects. Solving of these tasks requires the creation of a system of clear interaction between the state, business, science and education, based on the use of effective project management tools in the framework of innovation development, where the cluster approach should play an important role. The proposals of the application of the cluster approach in innovative projects can increase the efficiency of the use and implementation of innovative developments in the manufacturing sector by enhancing pred ictability, meaningful interaction, coordination and accountability of stakeholders in the public sector and private business within the framework of implementing of innovative projects. The system of indicators of innovation development taking into account clusters in the implementation of the project takes into account the following elements: innovative production (the integration of innovations in existing production capacity of one of the large enterprises or the organization of a new small company, where the costs of implementation and use of the innovative pro duct are minimized); technology transfer (promotion of innovations); production financing (the idea must go through the phase of engineering development, the production of a layout, the production of a prototype production in order to become a commercial product, that requires funding); the po tential of knowledge (higher education institutions, research institutes, individual specialists working as individuals, a system of informally interacting colleagues from different institutions and universities); training of innovative personnel (improvement of knowledge and competencies, accompanied by the creation of a team for the development of innovative projects).
The methodical bases of cluster approach in innovative projects
Keywords: науково-технологічний кластер; синергетичний ефект; карта кластеру; конкурентоспроможність; technological cluster; synergistic effect; cluster map